Optimization of Temperature to Bacteriocin by Lactobacillus plantarum Against Methicillin-Resistant Staphylococcus aureus - Salsabilla, Azizah Balqis; Suryani, Lilis (Universitas Muhammadiyah Yogyakarta, 2025)
Introduction: Methicillin-resistant Staphylococcus aureus (MRSA) is a pathogenic bacterium that is resistant to antibiotics. MRSA causes skin and soft tissues, lungs, blood flow, endocarditis, and osteomyelitis. The rate of MRSA infection in the world is 14.69% and in Indonesia by 25%-65%. They have resistance to beta-lactam antibiotics, penicillin, cephalosporin, and tetracycline. Bacteriosin is produced by lactic acid bacteria. The bacteriosins produced by Lactobacillus Plantarum has the ability to inhibit the growth of positive gram bacteria. Purpose: The study aims to knwoing how the temperature affects the bacteriologic activity produced by Lactobacillus plantarum affects the MRSA. Methode: The study employed quasi-experimental laboratory methods. Lactobacillus plantarum is grown on De Man Rogosa and Sharpe (MRS) Liquid media for 48 hours. Bacteria at 6000 RPM can be traced to a bacterium through a bacterium. The fluid formed was tested by its antibacterial effect on MRSA bacteria using the Kirby Bauer method. Bacteria are treated with different temperatures; 40°C, 60°C, 80°C, and 100 °C. The diameter of the obstructive zone formed during the testing process is measured by a millimeter. The data is analyzed by ANOVA methods. Finding: The bacteria generated by Lactobacillus plantarum on the MRSA showed an average diameter of the inhibition zone of 5.63 mm. The spectrum of the largest antibacterial activity indicates that the bacteria is heated at 60 °C temperature. Conclusion: The study showed results that the temperature did not affect the bacteria's antibacterial activity that the Lactobacillus plantarum produced on the MRSA. Originality/Implication: The results of this study prove that variations in temperature treatment do not affect the bacteria generated by the Lactobacillus plantarum in impeding or killing MRSA.